Pengaruh Harga dan Lokasi Terhadap Keputusan Pemilihan Kos di Kota Singaraja - Fitria, Ursila; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to determine the process of testing the influence of price and location on the decision to choose a boarding house in Singaraja City, either partially or simultaneously. In this research, the population used is people in Singaraja City who have used or are currently using boarding house rental services. The sampling technique uses non-probability sampling with purposive sampling technique. The number of respondents in this study was 120 people. This research uses quantitative data with data collection methods through questionnaires. Data processing uses the help of the Statistical Package for The Social Science (SPSS) version 16.0 program. The data analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The research results show that (1) partially price has a positive and significant effect on the decision to choose a boarding house in Singaraja City, (2) partially location has a positive and significant effect on the decision to choose a boarding house in Singaraja City, and (3) simultaneously price and location have a positive and significant effect on purchasing decisions in Singaraja City.